2017
DOI: 10.1007/s10557-017-6727-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Management of Statin-Associated Symptoms in Clinical Practice: Extension of a Clinician Survey to 12 Further Countries

Abstract: PurposeStatins are the first-choice pharmacological treatment for patients with hypercholesterolemia and at risk for cardiovascular disease; however, a minority of patients experience statin-associated symptoms (SAS) and are considered to have reduced statin tolerance. The objective of this study was to establish how patients with SAS are identified and managed in clinical practice in Austria, Belgium, Colombia, Croatia, the Czech Republic, Denmark, Portugal, Switzerland, Russia, Saudi Arabia, Turkey, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…42 In contrast to these findings, a cross-sectional study from the PALM registry in the USA found that 41.8% of current statin users and 63.2% of former statin users complained of at least one symptom associated with statin therapy. 13 Moreover, a multinational clinician web-based survey was conducted in two different studies which described that, according to physicians, the estimated percentage of patients unable to tolerate statins was 6% (2%-12% among 13 countries) 49 and 2.7% (1.1%-4.8% among 12 countries), 50 with muscular symptoms being the most common overall. 49 50 The differences in the definitions and reporting of ADRs may account for the variations in the frequency in our review.…”
Section: Discussionmentioning
confidence: 99%
“…42 In contrast to these findings, a cross-sectional study from the PALM registry in the USA found that 41.8% of current statin users and 63.2% of former statin users complained of at least one symptom associated with statin therapy. 13 Moreover, a multinational clinician web-based survey was conducted in two different studies which described that, according to physicians, the estimated percentage of patients unable to tolerate statins was 6% (2%-12% among 13 countries) 49 and 2.7% (1.1%-4.8% among 12 countries), 50 with muscular symptoms being the most common overall. 49 50 The differences in the definitions and reporting of ADRs may account for the variations in the frequency in our review.…”
Section: Discussionmentioning
confidence: 99%
“…However, muscle-related side effects of statin treatment are frequently reported. Interestingly, one of the rare statin-associated side effects is immune-mediated necrotizing myopathy (IMNM) [ 55 ], reviewed by [ 56 ]. IMNM is diagnosed by the presence of muscle fibres necrosis and degeneration, and is correlated with CK level and muscle strength [ 56 , 57 ].…”
Section: Pathological Mechanisms Underlying Lipid-lowering Drug-induced Myopathiesmentioning
confidence: 99%
“…Lipid-lowering medication has undergone a revolutionary development since the introduction of statins ( Hirakawa and Shimokawa, 2001 ). However, severe side effects (e.g., muscle injury) have hindered further clinical application ( Rosenson et al, 2017 ; White et al, 2020 ). Therefore, more attention has been paid to the research and development of drugs with lower toxicity and greater efficacy, especially those derived from natural products.…”
Section: Introductionmentioning
confidence: 99%